Unipolar Voltage Abnormality is Associated with Greater Left Ventricular Dysfunction in Ischemic Cardiomyopathy. (4th December 2013) - ALDHOON, BASHAR; FRANKEL, DAVID S.; HUTCHINSON, MATHEW D.; CALLANS, DAVID J.; EPSTEIN, ANDREW E.; DIXIT, SANJAY; RILEY, MICHAEL P.; LIN, DAVID; GARCIA, FERMIN C.; SUPPLE, GREGORY E.; COOPER, JOSHUA M.; BALA, RUPA; et al.
Unipolar Voltage Mapping in ICM Introduction Following myocardial infarction (MI), left ventricular function is determined by cardiac remodeling occurring in both infarcted and noninfarcted myocardium (NIM). Unipolar voltage mapping may detect remodeling changes in NIM that are associated with the left ventricular ejection fraction (LVEF). We aimed to identify (1) unipolar voltage characteristics in patients with chronic MI, and (2) association of voltage abnormalities with degree of left ventricular dysfunction (LVD). Methods and Results Two groups of patients with ischemic cardiomyopathy (ICM) who underwent LV endocardial mapping during catheter ablation for ventricular tachycardia (VT) between January 2010 and December 2012 were studied. The first group (19 males) had mild to moderate LVD (M‐LVD, LVEF >35%) and was matched for age, sex, infarction size, and infarction location with 10 males who had severe LVD (S‐LVD, LVEF <35%). Both bipolar and unipolar endocardial abnormal voltage areas were measured and compared between groups. Abnormal bipolar area was comparable in both groups (30 ± 8% in the S‐LVD group vs 28 ± 8% in the M‐LVD group; P = 0.5). Total abnormal unipolar voltage area was significantly larger in the S‐LVD group (57 ± 14% vs 43 ± 13%; P = 0.02). The abnormal unipolar voltage area within the normal bipolar voltage area was greater in the S‐LVD group (26 ± 11% vs 15 ± 16%; P = 0.03). In receiver operating characteristic curve analysis, an 18.0% cut‐off value for abnormal unipolar area within NIM identified severe LVD, with 90% sensitivity and 79% specificity (area under the curve 0.821). Conclusions Patients with ICM and severe LVD have larger areas of unipolar voltage abnormality in the noninfarcted tissue than patients with M‐LVD.